Grazing Resources of Rajasthan 1. Grassland Types of the Alluvial Plains - Shankarnarayan, K. A.; Satyanarayan, Y. (Indian Forester, 1964)
A brief account of the environment of the Centual Luni Basin in western Rajasthan is given. By line transect and chart quadrat studies, five grassland type have been distinguished in the alluvial plains, viz., (1) Sehima-Dichanthium type, (2) Cenchrus type, (3) Eleusine type, (4) Cynodon type, and (5) Aristida type. The floristic composition and analytical characters for each type are given in detail. The majority of the grasslands are in a degraded condition. The Sehima-Dichanthium and the Cenchrus types can be considered as "excellent" condition class; the Eleusine and Cynodon types as "fair" and the Aristida type as "poor" condition class